Determanation of Several Biochemical Markers in Sera of Patients with Kidney Diseases - Farhan, Layla O (Al-Nahrain Journal of Science, 2013)
Abstract: Renal failure is a medical condition from which the kidneys fail to adequately filter toxins and waste products from the blood. Renal failure is described as a decrease in the glomerular filtration rate. Biochemically, renal failure is typically detected by an elevated serum creatinine level. Problems frequently encountered in kidney malfunction include abnormal fluid levels in the body, deranged acid levels, abnormal levels of potassium, calcium, phosphate, and (in the longer term) anemia as well as delayed healing in broken bones. Depending on the cause, hematuria and proteinuria may occur. Long-term kidney problems have significant repercussions on other diseases, such as cardiovascular disease. The present study aim to evaluate several biochemical markers in Patients with Kidney Diseases and effect of these parameters in development the disease. Laboratory investigations including Renal function tests (RFT), fasting blood glucose, S. calcium, total protein, Uric acid, S. potassium, S. Sodium, and (MDA) as lipid peroxidation biomarker, gonadal Harmony had been measured in male and female with renal failure. Blood samples were obtained from the patients and matching group of healthey volunteer subjects were consideved as control group who came to the Al-Yarmok hospital for health checkup. There were significant difference in fasting blood glucose, Serum urea ,creatinine, S. calcium, S.sodium, MDA and uric acid in the patients whene compared to control group. MDA showed significantly increased between men and women groups (P<0.01). There was a negative correlation between MDA [μ mol/L] with Potassium [mg/dl/] (r=0.63, p<0.091), and MDA with calcium [mg/dl/] (r=0.58, p<0.019), respectively in patients group while no correlation was found among control subjects. MDA may play a role in development the kidney disease so more study may be need to stady MDA and another antioxdent to determine effect of them in the kidney disease.